1999
DOI: 10.1002/(sici)1521-4141(199905)29:05<1626::aid-immu1626>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Thyroglobulin monoclonal antibody cross-reacting with thyroperoxidase induces in syngeneic mice anti-idiotypic monoclonal antibodies with dual autoantigen binding properties. The intertope hypothesis

Abstract: Autoimmune thyroid diseases are characterized by antibodies (Ab) directed to thyroglobulin (Tg) and thyroperoxidase (TPO). Some of them, TGPO Ab, are Tg Ab with an interspecies idiotype (Id) reacting with TPO. Taking advantage of a carefully studied TGPO monoclonal antibody (mAb), we examined the basis of the hypothesis that TPO Ab would ultimately derive from TGPO Ab through idiotypic induction. We repeatedly immunized naive, syngeneic mice with the TGPO mAb and we derived three novel mAb directed to both Tg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Subsequently, Ruf et al . [17,18] concluded that anti‐Tg/TPO autoantibodies react with the two antigens via different sites of antibody variable region. Binding with Tg is realized via the paratope (antigen‐binding site), while TPO is bound via an idiotypic structure, away from the paratope, which is present in some of the human anti‐Tg autoantibodies as well as in murine monoclonal antibodies with the same epitope specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Ruf et al . [17,18] concluded that anti‐Tg/TPO autoantibodies react with the two antigens via different sites of antibody variable region. Binding with Tg is realized via the paratope (antigen‐binding site), while TPO is bound via an idiotypic structure, away from the paratope, which is present in some of the human anti‐Tg autoantibodies as well as in murine monoclonal antibodies with the same epitope specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental approaches involving the generation of monoclonal antibodies from immunized mice provide support for the TgPOAb hypothesis (11,12). However, isolation of bispecific human monoclonal Ab, rather than monoclonals from immunized mice, would definitively establish the existence of TgPOAb in human disease.…”
mentioning
confidence: 99%